O livro que divulgou o papiro Rhind no Brasil - Martins, Juliana [UNESP] (2015)
This dissertation is the result of a research study in the history of mathematics with the main objective of presenting an analysis of the book O mais antigo documento matemático conhecido (papyro Rhind), written by Eugênio de Barros Raja Gabaglia and published in Rio de Janeiro in the year 1899. Most of the text consists of the study of the book of Gabaglia, in which, in addition to considering the content itself we situate the analysis in the historical context in which the text was written. The procedures for the study evolved as the text was read. The analysis was based on two main types of literature: that which deals with the Rhind papyrus and ancient Egyptian mathematics, and, on the other hand, the historical theories of Fernand Braudel's and Michel de Certeau. The analysis is presented by means of comments the nature of which at times is explanatory, complementary, or comparative. The results of this work imply two kinds of final considerations: firstly Gabaglia's book reflects a broad and up-to-date knowledge of the author on the subject proposed, which undoubtedly deserves the prominence it has, given the time and place of publication. In addition, the development of the study provided a relevant approach to ancient Egyptian mathematics, in particular it was possible to come to know and understand the calculus methods and procedures employed in ancient Egyptian civilization which, like Gabaglia, we have come to admire greatly